Teacher education and dreams about classroom 3.0 (Revista Internacional de Formação de Professores, 2016)
In this work we approach, from a cultural and educational perspective, the relation between the educative institutions and their technological environments. The goal is to analyze the empowerment of the different school agents through reflexive experience, especially teachers. The methodology we used is based on strategies of meta-evaluation of our own fieldwork, focusing mainly on the School 2.0 institutional programs and the digitalization of the curricular contents. One of the conclusions is that the growing presence of technologies in schools does not correspond to a real renovation of classrooms methodologies nor to more thoughtful and emancipating practices.
Keywords: Educational policy, use of technology in schools, teaching methods, innovation.